Hyponatremia due to excessive water intake in COVID-19 patients: case series study - Ahmad Nasrat Al-juboori; Amira Al Hail; Zaid Ahmad Al-juboori (SpringerOpen, 2022)
Abstract Background Literatures revealed syndrome of inappropriate antidiuretic hormone (SIADH) as the most common mechanism of hyponatremia in COVID-19. However, it is important to rule out other etiologies of hyponatremia. Methods This is a case series, retrospective study. Four patients were reviewed from the Mesaieed Hospital, Hamad Medical Corporation, Qatar. The patients were admitted during the second wave of pandemic because of mild to moderate COVID pneumonia. The patients received medications according to the protocol; after few days of treatment, their blood laboratory results showed hyponatremia; as compared to the initial readings, hyponatremia workup excluded SIADH. History revealed that the patients were drinking large amounts of water, around 4-5 L/day, due of certain reasons: one patient had dysgeusia, and the other three patients thought that excessive drinking of water is beneficial for COVID-19 infection. Results The hyponatremia level was less than 135 mmol/L, other laboratory tests excluded SIADH, and the provisional diagnosis was dilutional hyponatremia. Male/female ratio was 3/1, age from 29- to 45-year-old patients with no associated comorbidities. Fluid restriction up to 1.5 L/day showed dramatic improvement of their sodium blood level. The patients are discharged in a stable condition. Conclusions In COVID-19 patients, hyponatremia not only is secondary to SIADH but can also be due to other etiologies. Hyponatremia can be induced by excessive water drinking and considered an extremely rare reported cases.